Shylock Hanna - he is bound to have his pound of flesh - Opper, Frederick Burr (N.Y. : Published by Keppler & Schwarzmann, 1897)
Print shows Marcus A. Hanna as Shylock, wearing a robe, holding a paper that states "Understanding between Wm. McKinley and Mark Hanna. The aforesaid Mark Hanna shall have the Dictation of all Ohio Appointments, etc., etc."; hanging from his waist is a purse labeled "Boodle" and a knife labeled "Patronage Knife", and extending from his pocket are balance scales.
Title from item.
Illus. from Puck, v. 41, no. 1064, (1897 July 28), cover.
Copyright 1897 by Keppler & Schwarzmann.
Keywords: Shylock (Fictitious character); Political patronage; Usury; Avarice